Trade-off Pareto optimum design of an innovative curved damper truss moment frame considering structural and non-structural objectives. (December 2020) - Fathizadeh, S.F.; Dehghani, S.; Yang, T.Y.; Noroozinejad Farsangi, E.; Vosoughi, A.R.; Hajirasouliha, I.; Takewaki, I.; Málaga-Chuquitaype, C.; Varum, H.
Abstract: This research aims to develop a novel and cost-effective seismic force-resisting system called "curved damper truss moment frame" (CDTMF) by coupling the recently developed curved dampers (CDs) with conventional steel trusses. In this proposed system, the CDs are adopted as primary fuses, while semi-rigid connections are used as secondary fuses to dissipate the input seismic energy through a two-phased energy dissipation mechanism called the equivalent energy design procedure (EEDP). To validate the adequacy and feasibility of incorporating the CDTMF system in multi-story framed structures, the multi-objective NSGA II optimization technique was applied to the optimum seismic design of selected CDTMF prototypes. Their seismic performance was then compared with the recently proposed buckling restrained knee braced truss moment frame (BRKBTMF) systems, which were designed based on the same procedure to make a consistent comparison. This comparison was based on the results of nonlinear static analysis (pushover), nonlinear time history analysis (NTHA) and incremental dynamic analysis (IDA) on three-, six- and nine-story steel framed structures (low- to mid-rise systems). Since damage to non-structural acceleration-sensitive elements would depend on the floor acceleration, and because the main cause of damage in non-structural displacement-sensitive elements and structural members is generally due to the story drift, the objective functions of the optimization process were the median maximum story drift and the peak floor acceleration. In order to achieve the two-phased energy dissipation mechanism, the primary constraints (PCs) and secondary constraints (SCs) corresponding to the primary and secondary fuses are applied. The outcomes of the pushover analysis showed that the optimal CDTMF structures exhibited higher ductility and energy dissipation capacity compared to the BRKBTMFs. The results of the nonlinear dynamic analysis also indicated that the newly proposed CDTMF system can control the roof displacement, story drift, and roof acceleration during an earthquake excitation more efficiently than the BRKBTMF system. Finally, the outputs of the IDA show that the CDTMFs can fulfilled the FEMA P695 code requirements. Hence, it can be considered as a reliable seismic force resisting system.